Central nervous system depressant effect of ethanol extract of Senna spectabilis (DC.) H.S.Irwin & Barneby in mice - Wiwied Ekasari; Retno Widyowati; Tutik S. Wahyuni; Suciati; Rice D. Oktarina; Chrismawan Ardianto; Elsa S. Prameswari; Windri A. A. Suri; Alfaniady I. Kurnia; Rahma K. Wirabuana; Vita M. A. Angembani; Ram K. Sahu (GarVal Editorial Ltda., 2023)
Context: Senna spectabilis (DC.) H.S.Irwin & Barnebywhich belongs to Fabaceae family is widely used traditionally in the treatment of various diseases and disorders such as constipation, insomnia, anxiety, epilepsy, malaria and skin diseases. Aims: To investigate the central nervous system (CNS) depressant effect of 70% ethanol extract of S. spectabilis leaves (70SSEE) using different neuropharmacological models in mice. Methods: The CNS depressant effect of 70SSEE was investigated by the classical models of depression as elevated plus maze (EPM), hole cross (HC), and thiopental sodium (TS)-induced sleeping time tests in mice. The EPM test was used to assess the anxiolytic activity of 70SSEE at doses of 10, 50, and 100 mg/kg, while HC and TS-induced sleeping time tests at doses of 100, 250, and 500 mg/kg were used to assess the locomotor and sedative activity in mice. Results: In EPM test, 70SSEE at doses of 50 and 100 mg/kg significantly (p<0.05) increased the number of open arm entries and time spent in open arm by mice compared to controls. In HC test, 70SSEE significantly inhibited the movement of animals across the hole in a dose-dependent manner. In addition, the administration of 70SSEE to mice significantly (p<0.05) decreased sleep latency time and increased sleep duration of TS-induced mice. Conclusions: 70SSEE has CNS depressant effects which is a rational explanation for its use in traditional medicine. From these findings, it is hoped that this plant could be used in the treatment of various neurological disorders, including anxiety and insomnia.